Subspecies and Distribution. O.d.dalliNelson,1884—Alaska,Canada(YukonTerritory,extremeWNorthwestTerritoriesandextremeNWBritishColumbia). O.d. stonei]A. Allen, 1897 — Canada (Yukon Territory, N British Columbia). in Bovidae - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2011)
Subspecies and Distribution. O.d.dalliNelson,1884—Alaska,Canada(YukonTerritory,extremeWNorthwestTerritoriesandextremeNWBritishColumbia). O.d. stonei]A. Allen, 1897 — Canada (Yukon Territory, N British Columbia). Published as part of Don E. Wilson & Russell A. Mittermeier, 2011, Bovidae, pp. 444-779 in Handbook of the Mammals of the World – Volume 2 Hoofed Mammals, Barcelona :Lynx Edicions on page 695, DOI: 10.5281/zenodo.6512484